Estudio de depósitos de tsunamis en la Laguna el Potosí, Petatlán Guerrero - Mejía Ángeles, Catalina (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
In this paper are presented the results of studies of tsunami deposits through the analysis of four cores obtained in the el Potosi lagoon, located in Petatlan Guerrero. Two cores were obtained in the southwestern part of the lagoon, 3.55 km away of the coastline (LBP-13-I, LBP-13-II), the remained two were obtained in the southeast part with closer distances to the line coast (LBP-13-III, LBP-13-IV). All the samples were analyzed using different proxies from geological (e.g. lithology, stratigraphy, 14C), geochemical (X-Ray Fluorescence, Total Organic Carbon, Total Inorganic Carbon), Magnetic (Magnetic Susceptibility) and mineralogical (XRD, Scanning Electron Microscopy and Infrared Spectrometry), with a sampling every 10 cm and where significant changes were observed. The magnetic susceptibility was recorded at 2 cm intervals in each core. XRF analysis allowed defining the percentage proportion of major chemical compounds such as Al2O3, Fe2O3, Na2O and CaO. Those are indicators of a marine incursion related to a tsunami event. Regarding the mineralogical characterization, the results of XRD, SEM and EIR agree that the sediments contain a mixture of mineral phases, where the main species found are Epidotes (vesuvianite), pyroxenes (diopside), amphiboles (actinolite), tourmaline (dravite) and chlorine, halite, sylvite, illite, halloysite and montmorillonite (7 to 10 Ångström). These mineral species are indicators of tsunami deposits. By analyzing the different proxies for the core LBP-13-I, located 3.55 km of the coastline, a deposit related to a marine incursion was identified at the unit I of 70-35 cm depth with an age of 2740 to 2490 BP, in this deposit we found a high content of Fe2O3t, Al2O3, Na2O, CaO, and a low content of TOC.

En el presente trabajo se presentan, los resultados de estudios de depósitos de tsunamis a través del análisis de cuatro núcleos obtenidos en la Laguna El Potosí Petatlán, Guerrero. Dos de los núcleos se obtuvieron hacia el SW a una distancia de 3.55 km de la línea de costa (LBP-13-I, LBP-13-II), los otros dos se obtuvieron hacia el SE con distancias más próximas hacia la línea de costa (LBP-13-III, LBP-13-IV). Todas las muestras se analizaron con diferentes proxies geológicos (litología, estratigrafía, 14C), geoquímicos (Fluorescencia de Rayos X, Carbono orgánico total, Carbono inorgánico total,) magnético (Susceptibilidad Magnética), y mineralógicos (Difracción de rayos X, Microscopia Electrónica de Barrido, y Espectrometría de Infrarrojo), con un muestreo a cada 10 cm y donde se observaron cambios importantes. La susceptibilidad magnética se registró a cada 2 cm en cada uno de los núcleos. El análisis de FRX, permitió definir la proporción en porcentaje de elementos químicos mayores de los cuales el, Al2O3, Fe2O3, Na2O, CaO, son indicadores de una incursión marina generada por tsunami. Respecto a la caracterización mineralógica, los resultados de DRX, MEB y EIR coinciden en que los sedimentos contienen una mezcla de fases minerales, donde las principales especies encontradas son epidotas (vesuvianita), piroxenos (diópsido), anfíboles (actinolita), turmalina (dravita), así como cloro, halita, silvita, ilita, montmorillonita y halloysita 7 y 10 Ångström, que son características de depósitos de tsunamis. Mediante el análisis de los distintos proxies para el núcleo LBP-13-I ubicado a 3.55 km sobre la línea de costa, indicando una incursión marina situada en la unidad I de 70 a 35 cm de profundidad con una edad de 2740-2490 A.P., en este nivel se encontró alto contenido de Fe2O3t, Al2O3, Na2O, CaO, bajo contenido de COT.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Geociencias y Planificación del territorio
Keywords: info:eu-repo/classification/cti/1; IIMM-M-2015-0454; Tsunamis; Sismo; Depósitos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5239